The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0123929
|View full text |Cite
|
Sign up to set email alerts
|

Associations of ABHD2 Genetic Variations with Risks for Chronic Obstructive Pulmonary Disease in a Chinese Han Population

Abstract: The human α/β hydrolase domain-containing protein 2 gene (ABHD2) plays a critical role in pulmonary emphysema, a major subset of the clinical entity known as chronic obstructive pulmonary disease (COPD). Here, we evaluated genetic variation in the ABHD2 gene in a Chinese Han population of 286 COPD patients and 326 control subjects. The rs12442260 CT/CC genotype was associated with COPD (P < 0.001) under a dominant model. In the former-smoker group, the rs12442260 TT genotype was associated with a decreased ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…ABHD2 participates in virus propagation and the modulation of the immune response, for which it was identified as a potential target of anti-hepatitis B drugs [75]. Interestingly, genetic variations in this gene have been associated with obstructive pulmonary disease in a Chinese Han population and age-related pulmonary emphysema in mice [76]. Moreover, the expression of ABHD2 was identified as a discriminating feature between smokers and non-smokers [77].…”
Section: Discussionmentioning
confidence: 99%
“…ABHD2 participates in virus propagation and the modulation of the immune response, for which it was identified as a potential target of anti-hepatitis B drugs [75]. Interestingly, genetic variations in this gene have been associated with obstructive pulmonary disease in a Chinese Han population and age-related pulmonary emphysema in mice [76]. Moreover, the expression of ABHD2 was identified as a discriminating feature between smokers and non-smokers [77].…”
Section: Discussionmentioning
confidence: 99%
“…The data regarding the number of exons were obtained from BioGPS, and the data regarding the relatively high expression in normal human tissues were primarily obtained from the BioGPS portal and the reported references. protein name molecular weight (kDa) aliases gene location in humans number of exons relatively high expression in normal human tissues (BioGPS) related function or role in disease ABHD1 45 LABH1 2p23.3 9 testis, sperm saphenous related to oxidative stress in mouse and rat models [ 29 32 ]; expression downregulation is driven by hepatic steatosis and insulin resistance induced by Notch signalling [ 33 ] ABHD2 48 HS1–2, LABH2, PHPS1–2 15q26.1 16 prostate, lung, NK cells, whole blood a glyceridase and ester hydrolase cleaving 2AG and leading to sperm hyperactivation in a progesterone-dependent manner [ 34 36 ]; an androgen-regulated gene promoting prostate cancer growth and resistance to chemotherapy [ 37 ]; essential for the reproduction of HBV [ 38 , 39 ]; involved in calcium transfer from the endoplasmic reticulum to mitochondria [ 40 ] and chronic obstructive pulmonary disease (COPD) in a Chinese Han population [ 41 ]; associated with anoikis resistance in ovarian cancer [ 7 ] and possibly associated with tumorigenesis in hepatocytes, stomach cells and colon cells [ 42 , 43 ] ABHD3 46 LABH3 18q11.2 12 colon, small intestine, whole blood a brain serine hydrolase related to the activation of the endocannabinoid system [ 44 ]; a lipase playing the role of...…”
Section: Research Progress Related To the Abhd Family Membersmentioning
confidence: 99%
“…ABHD2 was found to be a critical gene in chronic obstructive pulmonary disease (COPD) by evaluating the genetic variation in the ABHD2 gene among Han Chinese COPD patients and normal controls [ 41 ]. The analysis of the DNA methylation data of genes throughout the genome showed that COPD is associated with DNA methylation at the CpG sites of the ABHD16B gene [ 96 ].…”
Section: Research Progress Related To the Abhd Family Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…Through wavelet coherence analysis, [ 14 ] examines Bitcoin price formation and the main drivers of price. The study shows that factors such as “use in trade, money supply and price level” have an impact on long term price.…”
Section: Introductionmentioning
confidence: 99%